Contribution to the Flora of the Dangs Forest in Gujarat - Chavan, A. R.; Oza, G. M. (Indian Forester, 1966)
The plants from the Dangs Forest given here are additions to the earlier published records on the area. The note will help to include localities hitherto unknown for these plants, in the revision of the Cooke's Flora of Bombay.